Acclimation potential of Acropora to mesophotic environment. (March 2023) - Tavakoli-Kolour, Parviz; Sinniger, Frederic; Morita, Masaya; Harii, Saki
Abstract: Mesophotic coral ecosystems may serve as a refuge for reef-building corals to survive the ongoing climate change. Distribution of coral species changes during larval dispersal. However, the acclimation potential in the early life stages of corals at different depths is unknown. This study investigated the acclimation potential of four shallow Acropora species at different depths via the transplantation of larvae and early polyps settled on tiles to 5, 10, 20, and 40 m depths. We then examined physiological parameters, such as size, survival, growth rate, and morphological characteristics. The survival and size of juveniles of A. tenuis and A. valida at 40 m depth were significantly higher than those at other depths. In contrast, A. digitifera and A. hyacinthus showed higher survival rates at shallow depths. The morphology (i.e., size of the corallites) also varied among the depths. Collectively, the shallow coral larvae and juveniles displayed substantial plasticity at depth. Highlights: Four reef-building Acropora species in the shallow reef have acclimation potential to deeper areas. The survival rates in the deeper area were different among species. The morphology of juveniles (size of the corallites) differed among the depths. The shallow species may acclimate and expand their habitat to the deeper areas, where water temperature is cooler.